Grammar in Art - Segel, Edward; Boroditsky, Lera (Frontiers in Psychology, 2011)
Roman Jakobson (1959) reports: “The Russian painter Repin was baffled as to why Sin had been depicted as a woman by German artists: he did not realize that “sin” is feminine in German (die Sünde), but masculine in Russian (грех).” Does the grammatical gender of nouns in an artist’s native language indeed predict the gender of personifications in art? In this paper we analyzed works in the ARTstor database (a digital art library containing over a million images) to measure this correspondence. This analysis provides a measure of artists’ real-world behavior. Our results show a clear correspondence between grammatical gender in language and personified gender in art. Grammatical gender predicted personified gender in 78% of the cases, significantly more often than if the two factors were independent. This analysis offers a new window on an age-old question about the relationship between linguistic structure and patterns in culture and cognition.